Awareness of autism among parents / Jaida Najihah Jamidin ... [et al.] - Jamidin, Jaida Najihah; Zafarulhisham, Nur Irdina Izzati; Abd Majid, Nur Solehah; Daud, Nur Syuhaida (UiTM Cawangan Johor, 2019)
Autism is a complex neurobehavioral condition that includes impairments in social interaction, developmental language and communication skills combined with rigid and repetitive behaviours. The aims of this study are to identify the awareness level of Autism Spectrum Disorder (ASD) among parents that have a child with or without autism, and to investigate the relationship between the determinants (knowledge, role of government and community living) with the awareness of autism among parents by using ordinal regression analysis. The study reveals that a majority of parents have a medium level of awareness about autism. While the rest, have an equal percentage which is 20% respectively for high and low level of awareness about autism. From this study, it can be concluded that there is a relationship between knowledge and government role with the level of awareness of autism among parents.